Atrial fibrillation: a new facet of diabetes mellitus in the XXI century - Andrey Alexeevich Aleksandrov (Endocrinology Research Centre, 2011)
Congestive heart failure, diabetes mellitus, and ciliary arrhythmia are three epidemic cardiovascular conditions threatening the mankind in the XXIcentury. Ciliary arrhythmia is the commonest disturbance of cardiac rhythm characterized by inability of the atrium to maintain coordinated contractions.The importance of ciliary rrhythmia as a problem facing public heath services is underlain by its role as a risk factor of disturbed cerebralcirculation and severe cardiac insufficiency, the two most serious and costly cardiovascular complications influencing life expectancy of the affectedsubjects.